Investigation of a Novel Turboprop-Driven Aircraft Concept Including Future Technologies - Andreas Johanning and Dieter Scholz (Singapor ; Springer, 2017)
This paper presents a novel concept for a highly efficient and ecological propeller-driven aircraft. The aircraft has a high wing, T-tail, and two turboprop engines with large propeller diameters decreasing disc loading and therefore increasing propeller efficiency. The aircraft also features a strut-braced wing with natural laminar flow. It is shown that direct operating costs can potentially be reduced by about 17 % while reducing trip fuel mass and therefore CO2 emissions by about 36 % compared to the reference aircraft Airbus A320.
Keywords: Turboprop aircraft; Conceptual aircraft design; Aircraft design optimization; Strut-braced wing; Natural laminar flow